Natural and fallout radioactivity mapping of Kakrapar Gujarat site, India - S S Wagh; A K Patra; I V Saradhi; A Vinod Kumar (Radiation Protection and Environment, 2021)
This study presents the activity and outdoor gamma absorbed dose rates (terrestrial and cosmic) due to the naturally occurring (226Ra, 232Th, and 40K) and anthropogenic (137Cs) radionuclides around Kakrapar Gujarat site. The activity level (Bq/kg) in the soil ranged 5.7–48.4 for 226Ra, 9.7–28.0 for 232Th, 83.9–585.7 for 40K, and 0.2–4.6 for 137Cs, respectively. The mean concentration levels measured in Kakrapar soil from the naturally occurring radioisotopes are lower than the corresponding global average values. 137Cs activity in the soil is comparable with the preoperational period. The total effective dose rates in air outdoors ranged 17.2–78.1 μSv/y with the mean value of 32.8 μSv/y. The mean value of absorbed dose rate due to cosmic components was 37.5 nGy/h which is comparable to the worldwide reported values.